PENGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN PERMAINAN LETâS BE CREATIVE (LBC) PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII SMP IT NUR HIDAYAH SURAKARTA - Lailatul F, Isna Nur; Mardiyana, Mardiyana; Sari S, Dewi Retno (Journal of Mathematics and Mathematics Education, 2015)
Abstract: The aims of this study are: (1) to describe the process of jigsaw model with LBC game in polyhedra (cubes, cuboids, prisms and pyramids) learning materials at VIII grade of high school students. (2) to get the result of jigsaw model with LBC game are valid, practical use in learning, and effectively use in learning. The discussion in this study using a model of the development of four D Thiagarajan (4D) includes; definition phase (define), stage design (design), stage of development (develop), and the deployment phase (disseminate). The results of this developmental study are: (1) a valid model of jigsaw with LBC game which applied in polyhedra (cubes, cuboids, prisms and pyramids) learning materials of VIII grade Junior High School with an average score rate is 3,55 and include in very good criteria. (2) a practical model of jigsaw with LBC game with a practical implementative average score rate (before implementation) is 3,44 and include in very good criteria and the teacher stated that jigsaw model with LBC game can be implemented in the classroom. (3) an effective model of jigsaw with LBC game to be implemented in the classroom. The effectiveness of the model according to the creativity in solving the mathematic problem which treated with jigsaw model with LBC game is better than jigsaw model only, the assessment by the observer when the teaching and learning process using jigsaw model with LBC game is 3,1375 include in good criteria with reliability rate 87,83%. Studentsâ respond toward the model is adequate with total average rate 2,793 and include in adequate category. The teacher also gives positive statements that jigsaw model with LBC game is good, the students being active and LBC game attracts all of the students. According to the discussion result, it can be concluded that jigsaw model with LBC game fulfil the criteria validity, practicality, and effectivity.Keywords: Jigsaw model development with LBC game, creativity.